IMPLEMENTATION OF NUMBER HEAD TOGETHER (NHT) LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES OF CLASS VII-1 PUBLIC MIDDLE SCHOOL 5 TERNATE CITY ON NATURE MATERIAL OF INDONESIA. - Samsi Awal (USN Kolaka, 2019)
This study aims to determine the increase in student learning outcomes through the application of the learning model Number Head Together (NHT) on the material natural conditions of Indonesia, Public Middle School 5 Ternate City in 2013/ 2014. This type of research is classroom action research that follows the stages of research that start from action planning, implementation, observation, and reflection. The results showed that the Number Head Together learning model succeeded in improving student learning outcomes. this can be seen from the acquisition of student grades, namely there are 20 students (80%) who have not yet reached The Minimum Completeness Criteria and there are only 5 students (20%) who have achieved The Minimum Completeness Criteria in cycle I. In cycle II it increased to 19 students (76%) who reached The Minimum Completeness Criteria and only 6 students (24%) who have not yet reached The Minimum Completeness Criteria. Learning with the Number Head Together model can make students have the courage to ask questions, answer questions, discuss and cooperate with fellow group members, and can create an atmosphere of active, creative, and fun learning.